Sistem Pendidikan Islam di Lingkungan Keluarga dan Private Les “APIN” di Desa Karangmalang Kecamatan Ketanggungan Kabupaten Brebes: Sistem Pendidikan Islam di Lingkungan Keluarga dan Private Les “APIN” di Desa Karangmalang Kecamatan Ketanggungan Kabupaten Brebes - Mona; Mubayinah; Inayah , Khayyu (EDUCATIVA, 2023)
This research uses a qualitative method with a field research approach, namely the researcher goes directly to conduct research on the object to get factual research data. This research discusses the Islamic education system within the family. The background of this research is that the family has a very important role in educating their children and the family is also the first Islamic education institution for their children, because children are longer with their families than with their teachers at school. The child's character will also be formed to be good or bad depending on how the family educates, especially the parents. Family is the most comfortable place for children. Starting from the family, everything develops. The ability to socialize, self-actualize, argue, to deviant behavior. So, Islamic education in the family environment is very important to apply in educating children. In educating children, parents can also enter children into private lessons so that children can absorb their education more broadly. In educating children, sometimes parents are more often misunderstood if their children have been enrolled in an educational institution, parents think that they have lost responsibility in providing education to children, all of which are charged to the institution. Whereas parents should also support children in their education, especially Islamic education. The purpose of this study is to understand the Islamic education system in the family environment, so that parents can apply this system to their children. The results of this study state that families, especially parents, play a very important role in the education of their children so that children can get a positive education so that good children are created. Parents can also entrust their children in private lessons so that the child can get more material that he does not get in his family education.